EPR study of Cu2+ ions in the Pr0.5RE0.5Ba2Cu3O6 + x compounds in tetragonal phase at low temperatures - Guskos, N.; V. Likodimos; Koufoudakis, A.; Bojanowski, B.; Typek, J.; Wabia, M. (Journal of Magnetism and Magnetic Materials, 1995)
Powdered samples of the Pr0.5RE0.5Ba2Cu3O6 + x compounds, where RE Yb, Ho, Tm, Er, and Y, were investigated by the EPR technique at low temperatures in the range 2.8-20 K. In the EPR spectra of these non-superconducting materials in tetragonal phase, resonance lines arising from the exchange interaction of coupled pairs of divalent copper ions and Cu2+ in the tetragonal local crystal field symmetry were recorded. Apart from the usually observed ΔMs = 1 and ΔMs = 2 transitions for the CuCu system, rarely reported singlet-triplet transitions were detected as well. The exchange parameter J has roughly the same value of about 0.12 cm-1 for all investigated samples and the zero-field splitting parameter D is of the order of 0.013 cm-1. It is suggested that formation of Cu(1)OCu(2) copper coupled pairs is responsible for the observed EPR spectrum. © 1995.